Samarqand viloyatida agrosanoat klasterlarini hududiy joylashuvi va ixtisoslashuvi (SCIENCE and SOCIETY, 2024)
In this article explores the territorial location of agro-industrial clusters in Samarkand region, covering important data such as the state of agro-industrial clusters in the region and their location in the cross-section of districts, the types of existing clusters and the farms within agro-industrial clusters, the agricultural land attached to them.